2022
DOI: 10.1002/pc.26540
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tannic acid modified bamboo fiber on the performance of soybean bio‐asphalt/styrene‐butadiene‐styrene modified asphalt

Abstract: This study resolves the poor enhancement problem of high‐temperature performance and lower dissolution of styrene‐butadiene‐styrene (SBS) modified asphalt and soybean bio‐asphalt (SBA) (extracted from waste soybean oil) by tannic acid (TA) modified bamboo fiber (MBF). The rheological properties and microscopic morphologies of the modified asphalt and fibers were investigated by dynamic shear rheometer (DSR), multiple stress creep recovery (MSCR) tests, and Fourier transform infrared (FTIR) spectroscopy. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Based on the findings obtained by Jia et al [ 149 ], the inclusion of bamboo fibers in an asphalt mix at a proportion of 0.3% by mix weight remarkably improved the rutting and fatigue cracking resistance of the asphalt mix. Meng et al [ 150 ] found that amending bitumen with bamboo fibers, SBS, and soybean bio-asphalt at a dosage of 3% by bitumen weight led to better performance than the modified bitumen with 5% SBS in terms of rheological properties.…”
Section: Results and Analysismentioning
confidence: 99%
“…Based on the findings obtained by Jia et al [ 149 ], the inclusion of bamboo fibers in an asphalt mix at a proportion of 0.3% by mix weight remarkably improved the rutting and fatigue cracking resistance of the asphalt mix. Meng et al [ 150 ] found that amending bitumen with bamboo fibers, SBS, and soybean bio-asphalt at a dosage of 3% by bitumen weight led to better performance than the modified bitumen with 5% SBS in terms of rheological properties.…”
Section: Results and Analysismentioning
confidence: 99%
“…To examine the viscoelastic and rheological characteristics of modified asphalt binders, the Strategic Highway Research Program (SHRP) utilized dynamic shear rheology (DSR) (Bohlin CVO, Malvern Ltd.) capable of replicating the continuous and repetitive vehicle loading and unloading experienced on the road. 5 According to the SHRP specification (T315. AASHTO 2013), 4 various parameters of the original SBS-MA and modified asphalt with differing admixtures of fibers were measured using parallel plates with a diameter of 25 mm and a spacing of 1 mm, within a shear frequency range of 0.1-10 Hz and a scanning temperature range of 46-82 C. The parameters measured included the complex modulus (G*), phase angle (δ), and rutting factor (G*/sinδ).…”
Section: Dynamic Shear Rheology Testmentioning
confidence: 99%
“…Moreover, their chemical composition is similar to asphalt components, making them highly attractive for asphalt pavement applications. 8 Furthermore, given that asphalt is a highly viscous fluid derived from residues of petroleum distillation, 9 fibers added to asphalt-based composites can serve as crack arrestors, adsorbers, stiffeners, and stabilizers, 5 which can in turn enhance the overall performance of the final material. However, the smooth surface and chemical inertness 10 of the PET fibers lead to a weak interface with asphalt, making the fibers highly susceptible to interfacial debonding and pull-out.…”
mentioning
confidence: 99%
“…[27] FTIR can characterize information on changes in the molecular structure of the fiber. [28][29][30] In untreated jute fibers (JFU), the peak at 3422 cm À1 became wider due to the hydrogen bonded O-H groups of the cellulose and hemicellulose. [31,32] The peak at 2922 cm À1 were attributed to C H stretching of all hydrocarbon components of the jute fibers.…”
Section: Fourier Transform Infrared Spectroscopy Analysis Of Untreate...mentioning
confidence: 99%